Nonlinear Flexural and Torsional Vibrations of Axially Moving Orthotropic Web - K. Marynowski; Z. Kołakowski (Engineering Transactions, 2005)
A new approach to the analysis of the dynamic behaviour of an axially moving orthotropic web is presented. Mathematical model of the moving web system constitutes two nonlinear, coupled equations governing the transverse displacement and stress function. The results of numerical investigations show the solutions to the linearized and nonlinear problems. Free vibrations of the web with different initial streses are analyzed. The effect of orthotropy factor and axial transport velocity on transverse and torsional vibrations are presented.